2004
DOI: 10.1016/j.geothermics.2003.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of recent volcanic episodes at Phlegrean Fields (Italy): geochemical variations and ground deformation

Abstract: Phlegrean Fields is an active caldera structure, located at the periphery of Naples (Italy). After the last eruptive event (the Monte Nuovo eruption, in 1538), periodic episodes of unrest characterize the evolution of this volcanic district, involving seismic activity and slow ground motion (bradyseism). During unrest episodes, there have been significant changes in the composition of hydrothermal fluids discharged at La Solfatara fumarolic field. These unrest phenomena result from complex interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 34 publications
(17 reference statements)
4
69
0
Order By: Relevance
“…When hydrothermal fluids from a magma reservoir are injected into surrounding rocks, hydraulic head in the hydrothermal systems will rise and the ground will be uplifted (e.g. Todesco et al, 2004;Hurwitz et al, 2007;Rinaldi et al, 2010;Fournier and Chardot, 2012), while strain due to chamber inflation generally leads to a water level fall together with ground uplift. Temperature sensors in monitoring wells provide additional valuable information, as hydrothermal fluid injections should lead to relatively fast temperature effects compared to heat transferred from an inflating chamber or a dyke intruding through the crust, which would reach the aquifer much later -in fact, after the poroelastic response is already equilibrated.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When hydrothermal fluids from a magma reservoir are injected into surrounding rocks, hydraulic head in the hydrothermal systems will rise and the ground will be uplifted (e.g. Todesco et al, 2004;Hurwitz et al, 2007;Rinaldi et al, 2010;Fournier and Chardot, 2012), while strain due to chamber inflation generally leads to a water level fall together with ground uplift. Temperature sensors in monitoring wells provide additional valuable information, as hydrothermal fluid injections should lead to relatively fast temperature effects compared to heat transferred from an inflating chamber or a dyke intruding through the crust, which would reach the aquifer much later -in fact, after the poroelastic response is already equilibrated.…”
Section: General Considerationsmentioning
confidence: 99%
“…Numerical modelling of pressure changes in hydrological systems has focused on pressure and temperature transients in hydrothermal systems and resulting ground deformation due to the injection of hot magmatic fluids, using one-way coupling of solid deformation and porous flow (e.g. Todesco et al, 2004;Hurwitz et al, 2007;Hutnak et al, 2009;Rinaldi et al, 2010;Fournier and Chardot, 2012). Rutqvist et al (2002) have developed a two-way coupled code and applied it to problems related to carbon dioxide injection in aquifers and the disposal of nuclear waste in porous media.…”
mentioning
confidence: 99%
“…[4] Recent numerical modeling studies have indeed demonstrated that rates of GSD measured by geodetic techniques could theoretically be induced by poroelastic transients in the shallow hydrothermal system [Hurwitz et al, 2007;Todesco et al, 2004]. Todesco et al [2004] carried out simulations using a multiphase, multicomponent (H 2 O-CO 2 ) fluid to describe the recent evolution of a shallow (1.5 km deep) hydrothermal system in the Campi Flegrei Caldera (Italy), and Hurwitz et al [2007] carried out simulations using a single-component (H 2 O) fluid with the goal of determining the range of plausible conditions under which poroelastically induced GSD might occur.…”
Section: Introductionmentioning
confidence: 99%
“…Todesco et al [2004] carried out simulations using a multiphase, multicomponent (H 2 O-CO 2 ) fluid to describe the recent evolution of a shallow (1.5 km deep) hydrothermal system in the Campi Flegrei Caldera (Italy), and Hurwitz et al [2007] carried out simulations using a single-component (H 2 O) fluid with the goal of determining the range of plausible conditions under which poroelastically induced GSD might occur.…”
Section: Introductionmentioning
confidence: 99%
“…The TOUGH-FLAC simulator has been recently applied and tested over a wide range of research fields, such as carbon sequestration (e.g., Cappa and Rutqvist, 2012;Rinaldi and Rutqvist, 2013), nuclear waste disposal (e.g., Rutqvist and Tsang, 2012, and references therein), hydrothermal systems and volcanology (Todesco et al, 2004), as well as studies related to water injection in geothermal fields (e.g., Rutqvist et al, 2013a;Vasco et al, 2013).…”
Section: Model Setupmentioning
confidence: 99%